FEATURES OF SANATORIUM TREATMENT OF PATIENTS WITH SKIN DISEASES - Гладких, Надія; Дюдюн, Анатолій; Поліон, Наталья; Поліон, Микита (SWorldJournal, 2023)
Sanatorium treatment of dermatological patients is one of the important stages of patient management, especially for those suffering from common dermatoses that occur with frequent prolonged exacerbations and short-term remissions.Natural factors have a